Using Wattpad as a Digital Multimodal Composing of Narrative Text - Sari, Juliani Nur Mustika (RETAIN : Journal of Research in English Language Teaching, 2022)
Digital multimodal composing has an important role to improve EFL students' writing skills in this current situation because the "digital" media can use every time and everywhere. The goal of this study is to find out what tenth-grade students think about using digital multimodal composing in narrative writing. This study was conducted with 26 students from SMKN 10 Surabaya using a qualitative method. A grading rubric and a semi-structured interview were used as data sources. The research data is gathered through observation and interviews. The collected data from interviews were organized, analyzed, coded, and interpretedto analyzed the data. The data analysis was performed to assess the digital multimodal narrative text composition. Wattpad, as a digital multimodal composing medium, helps students understand the subject, makes the learning process more interesting, increases students' motivation, and improves their writing skills, according to this study. Although many students enjoy reading stories on Wattpad, some prefer to read narrative texts in textbooks, while others claim that Wattpad takes up a lot of storage on the device. It is recommended for EFL teachers to use digital multimodal composing to make the learning process more interesting and gain the students’ motivation learning English writing.